Menjaga Tatanan Internasional: Politik Luar Negeri Indonesia Menurut Perspektif Pluralisme Mazhab Inggris - Mohamad Rosyidin; Fendy Eko Wahyudi (Jurnal Ilmiah Hubungan Internasional, 2026)
Most scholarly analysis of Indonesia’s foreign policy has centered on realist and constructivist frameworks, largely overlooking its normative vision of world order. This paper fills this gap by examining Indonesia’s perspective through the lens of the English School. It argues that Indonesia’s conception of world order aligns with the pluralist strand of the English School, emphasizing a system where states interact with each other driven by national interests while upholding each other’s sovereignty. In order to preserve international order, states must not interfere domestic affairs of other countries and utilize dialogue through international institutions to resolve conflicts. The use of force violates international law and in turn brings about damage to the existence of international order. Consequently, despite its unique historical and cultural context, Indonesia’s worldview shares commonalities with Eurocentric models in International Relations. Keywords: Indonesia’s foreign policy, world order, pluralist, English School